Central pedagógica un espacio de apoyo a la gestión curricular de los docentes (Educational Perspectives Magazine (REPED), 2022)
The reflective work is presented through an innovative proposal regarding the creation of the Central Pedagogical, as a space that aims to support the teacher through a series of resources. The Central was equipped with leaming materials especially selected, organized and classified, to be available to teachers who are interested in elevating their teaching.The high school Nonato Coo had an idle and a dependent input is constituted as a fortress for the management of the teacher, respect to teaching materials and resources (support guides, textbooks, tests, etc.) The implementation period involved a lot of time for installation of fumiture, arrangements of doors, painting, decoration and organization of materials through the sorting sub textbooks 2008,corporate programs, and reading silent among others.After the previous stage, the project was presented to all General advice teachers also conducted in the Sector in the establishment, being present representatives of the Municipal Corporation Education Puente Alto. Regarding the accompanying curricular materials and resources involves creating support for the curriculum, considering and prioritizing the lowest resources and methodologies.During the beginning of the academic year 2009, the Central Pedagogical features a Computer and internet with wireless network, which has created a database with support guides, testing and power point in the different sectors and sub- sectors, with contení relevant to the teaching and pedagogical management of the Plans and Programs of the MENEDUC.
Keywords: Central Education, Management Education, Teachers